2003
DOI: 10.1016/s0040-6031(03)00144-8
|View full text |Cite
|
Sign up to set email alerts
|

The determination of activation energy from linear heating rate experiments: a comparison of the accuracy of isoconversion methods

Abstract: Model-free isoconversion methods are the most reliable methods for the calculation of activation energies of thermally activated reactions. A large number of these isoconversion methods have been proposed in the literature. A classification of these methods is proposed. Type A methods such as Friedman methods make no mathematical approximations, and Type B methods, such as the generalised Kissinger equation, apply a range of approximations for the temperature integral. The accuracy of these methods is investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
714
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,579 publications
(793 citation statements)
references
References 44 publications
10
714
0
7
Order By: Relevance
“…This activation energy should be equal to the activation energy for S phase formation, which can be derived from experiments which measure the rate of S formation at different temperatures. For the present analysis, the activation energy is obtained from DSC experiments performed on a 2024-T351 alloy at different heating rates using iso-conversion methods [57,58]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activation energy should be equal to the activation energy for S phase formation, which can be derived from experiments which measure the rate of S formation at different temperatures. For the present analysis, the activation energy is obtained from DSC experiments performed on a 2024-T351 alloy at different heating rates using iso-conversion methods [57,58]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…versus T 1 [57] in Fig.5(b), where p T is the peak temperature and β is the heating rate. (In Fig.5(b) an additional data point for heating rate ~5 K/s (25°C/min) is also included).…”
Section: Resultsmentioning
confidence: 99%
“…Fan [4] used a new method for the derivation of activation energies is proposed by Starink [5]. It was shown [5] that this method is an order of magnitude more accurate than the Kissinger and Ozawa methods [6].…”
Section: Experimental Measurements Of Thermite Heat Reactionmentioning
confidence: 99%
“…It has been shown that for analysis of linear heating experiments (heating at constant rate), highly accurate and reliable activation energy analysis methods can be obtained by applying accurate approximations of the temperature integral [10]. This derivation can be formulated as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Through applying a suitable approximation for the temperature integral on the right of the latter equation a range of well-known and lesser known isoconversion methods for activation energy analysis can be derived [10]. These methods include the Kissinger method [11], the Kissinger-Akahira-Sunose (KAS) method [12,13] (also termed the generalised Kissinger method), the Flynn-WallOzawa (FWO) method [14,15], a method described by Vyazovkin and co-workers [16,17] and 3 highly accurate methods developed by the present author [10,18,19].…”
Section: Introductionmentioning
confidence: 99%